A concepção de criança e alei de nove anos - Motta, Carolina Caires [UNESP]; Constantino, Elizabeth Piemonte [UNESP] (My University, 2010)
The historical analysis of the conception of child is essential to understand the speeches, public policies and actions that are set aside for them. The 20th century ´ social-economic changes and the consequent need for women's work produced a restructuring not only in the family, but also in the care and attention focused on childhood. The present article under the perspective of Cultural-historical approach aims to make a reflection about the conception of child in the educational context, especially in the face of recent public policies that favor education´s advance in state schools. Besides, they also intend to point out some consequences and possible problems that may arise with their implementation and discuss the implications for the teacher´s organization of methodological practice and the relationship between development and learning.

A análise histórica da concepção de criança é indispensável para se compreender os discursos, as políticas públicas e as ações que lhe são destinadas. As transformações socioeconômicas decorrentes do século XX e a consequente necessidade do trabalho feminino produziram reestruturações, tanto no âmbito familiar, como no âmbito do cuidado e atenção voltados à infância. O presente artigo, sob o enfoque da abordagem Histórico-Cultural, visa a fazer uma reflexão acerca da concepção de criança no contexto educacional, principalmente diante das recentes políticas públicas que privilegiam a antecipação da escolaridade, nas redes estaduais de ensino. Além disso, pretende apontar algumas consequências e eventuais problemas que podem surgir com a sua implantação, e discutir as suas implicações para a organização da prática pedagógica do professor e às relações entre desenvolvimento e aprendizagem.
The conception of child and the nine years’law
Keywords: Basic education of 9 years; Conception of Child; Anticipation of schooling; Historical-cultural perspective; Ensino Fundamental de 9 anos; Concepção de criança; Antecipação da escolaridade; Enfoque Histórico-Cultural